2017
DOI: 10.1071/he16054
|View full text |Cite
|
Sign up to set email alerts
|

Sitting ducks face chronic disease: an analysis of newspaper coverage of sedentary behaviour as a health issue in Australia 2000–2012

Abstract: Issue addressed This study examines how sedentary behaviour (too much sitting) was covered as a health issue by Australian newspapers and how physical activity was framed within this newspaper coverage. Methods Articles featuring sedentary behaviour published in Australian newspapers between 2000 and 2012 were analysed for content and framing. Main outcome measures were volume, number and content of newspaper articles; framing and types of sedentary behaviour; responsibility for the problem of and solutions to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
(20 reference statements)
1
16
0
Order By: Relevance
“…There is a notable increase in interest in the associations between time reallocation among movement-related behaviours and their relationship to health outcomes. While much media coverage has focused on the adverse effects of prolonged sedentary behaviour [ 93 ], evidence in this review suggests it would be more appropriate to shift the focus on the importance of reallocating time spent in sedentary behaviour to time spent in physical activity. The approach taken in this review broadens the physical activity behavioural arena, for both researchers and policymakers.…”
Section: Discussionmentioning
confidence: 99%
“…There is a notable increase in interest in the associations between time reallocation among movement-related behaviours and their relationship to health outcomes. While much media coverage has focused on the adverse effects of prolonged sedentary behaviour [ 93 ], evidence in this review suggests it would be more appropriate to shift the focus on the importance of reallocating time spent in sedentary behaviour to time spent in physical activity. The approach taken in this review broadens the physical activity behavioural arena, for both researchers and policymakers.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the most powerful driving force for the SB field is the idea that the harms caused by too much sitting cannot be countered by doing sufficient PA, an idea that has been promulgated by both mass media and segments of the research community. For example, a recent media analysis study31 found that almost 40% of SB-related stories in Australian newspapers stated that PA is irrelevant if a person sits for too long or that the benefits of PA are abolished by too much sitting. Despite the lack of any compelling evidence to support it, this idea was disseminated from the early days of SB research and is a view that is still in circulation 20 32…”
Section: Introductionmentioning
confidence: 99%
“…Using previously described methods, a content and frame analysis protocol was designed. This was pilot tested, and following revisions were used to code each news article.…”
Section: Methodsmentioning
confidence: 99%